Near infrared spectrometry for faecal fat measurement: comparison with conventional gravimetric and titrimetric methods. Issue 10 (October 1989) - Benini, L; Caliari, S; Guidi, G C; Vaona, B; Talamini, G; Vantini, I; Scuro, L A
Abstract : This investigation was aimed at comparing a new method for measuring faecal fat excretion, carried out with a semi-automated instrument by using near infrared analysis (NIRA), with the traditional titrimetric (Van de Kamer) and gravimetric (Sobel) methods. Near infrared analysis faecal fat was assayed on the three day stool collection from 118 patients (68 chronic pancreatitis, 19 organic diseases of the gastrointestinal tract, 19 alcoholic liver disease, 12 functional gastrointestinal disorders). A strict linear correlation was found between NIRA and both the titrimetric (r = 0.928, p less than 0.0001) and the gravimetric (r = 0.971, p less than 0.0001) methods. On homogenised faeces, a mean coefficient of variation of 2.1 (SD 1.71)% was found. Before homogenisation (where a mean coefficient of variation of 7% was found) accurate results were obtained when the mean of five measurements was considered. In conclusion, the assay of faecal fat excretion by the near infrared reflessometry appears a simple, rapid and reliable method for measuring steatorrhoea.